2023
DOI: 10.1038/s41598-023-28703-z
|View full text |Cite
|
Sign up to set email alerts
|

A regressive machine-learning approach to the non-linear complex FAST model for hybrid floating offshore wind turbines with integrated oscillating water columns

Abstract: Offshore wind energy is getting increasing attention as a clean alternative to the currently scarce fossil fuels mainly used in Europe’s electricity supply. The further development and implementation of this kind of technology will help fighting global warming, allowing a more sustainable and decarbonized power generation. In this sense, the integration of Floating Offshore Wind Turbines (FOWTs) with Oscillating Water Columns (OWCs) devices arise as a promising solution for hybrid renewable energy production. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In their work [97,98], the researchers explored the utilization of an MLP network for modeling a hybrid floating wave energy-wind turbine platform. Subsequently, they introduced a fuzzy logic control system to implement a structural controller aimed at mitigating undesirable vibrations within the platform.…”
Section: Data-driven Model-based Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In their work [97,98], the researchers explored the utilization of an MLP network for modeling a hybrid floating wave energy-wind turbine platform. Subsequently, they introduced a fuzzy logic control system to implement a structural controller aimed at mitigating undesirable vibrations within the platform.…”
Section: Data-driven Model-based Literature Overviewmentioning
confidence: 99%
“…First, Ref. [97] delved into the creation of a control-oriented regressive model for a hybrid FOWT with an oscillating water column wave energy converters platform. The primary objective was to leverage the predictive capabilities and computational simplicity of deep-layered MLP to develop a feasible, lightweight, control-oriented model in contrast to complex dynamical models.…”
Section: Data-driven Model-based Literature Overviewmentioning
confidence: 99%
“…Ahmad et al explored the application of an MLP network to model a hybrid floating wave energy-wind turbine platform and subsequently introduced a fuzzy logic control system to implement a structural controller aimed at mitigating undesirable vibrations within the platform [80,81]. The team employed OpenFAST and WAMIT for hydrodynamic modeling and the results showed that the MLP-based model could promise a simpler yet effective alternative to more complex nonlinear dynamical models for NREL 5 MW floating offshore wind turbines.…”
Section: Lian Et Al Developed An Mlp-based Regression Model To Relate...mentioning
confidence: 99%
“…Limited research has been conducted on creating surrogate models that accurately capture the dynamic response of offshore wind turbines. For instance, Ahmad et al 57 utilized artificial neural networks to develop a surrogate model for the aero‐hydro‐servo elastic performance of hybrid floating offshore wind turbines. The model was trained on mid‐fidelity data; however, there is a need to develop surrogates that can accurately capture extreme dynamic phenomena by utilizing high‐fidelity datasets.…”
Section: Introductionmentioning
confidence: 99%